Children’s Neglect of Probabilities in Decision Making with and without Feedback - Lang, Anna; Betsch, Tilmann (Frontiers in Psychology, 2018)
We investigated whether children prefer feedback over stated probabilistic information in decision making. 6-year-olds’, 9-year-olds’, and adults’ decision making was examined in an environment where probabilistic information about choice outcome had to be actively searched (N = 166) or was available without search (N = 183). Probabilistic information was given before choices as predictions of cues differing in validity. The presence of outcome feedback was varied. Six-year-olds, but not nine-year-olds were over-responsive to negative outcomes leading to choices biased by recent feedback. However, children did not systematically utilize feedback in choices. Irrespective of feedback, 6-year-olds fully and 9-year-olds partly neglected stated probabilistic information in their choices. When 6-year-olds chose systematically, they only relied on invalid information, which did not maximize outcomes. Nine-year-olds still applied invalid choice rules, but also choice rules based on probability. Results suggest that neglect of probabilities in complex decisions is robust, independent of feedback, and only starts to subside at elementary school age.